Recent progress on covalent organic framework materials as CO2 reduction electrocatalysts - Fan, Yang; Chen, Mengyin; Xu, Naizhang; Wang, Kaiqiang; Gao, Qiang; Liang, Jing; Liu, Yubing (Frontiers in Chemistry, 2022)
CO2 emission caused by fuel combustion and human activity has caused severe climate change and other subsequent pollutions around the world. Carbon neutralization via various novel technologies to alleviate the CO2 level in the atmosphere has thus become one of the major topics in modern research field. These advanced technologies cover CO2 capture, storage and conversion, etc., and electrocatalytic CO2 reduction reaction (CO2RR) by heterogeneous catalysts is among the most promising methods since it could utilize renewable energy and generate valuable fuels and chemicals. Covalent organic frameworks (COFs) represent crystalline organic polymers with rigid highly and conjugated structures and tunable porosity, which exhibit significant potential as heterogeneous electrocatalysts for CO2RR. This review briefly introduces related pioneering works in COF-based materials for electrocatalytic CO2RR in recent years and provides a basis for future design and synthesis of highly active and selective COF-based electrocatalysts in this direction.